2016
DOI: 10.25077/adj.v4i2.58
|View full text |Cite
|
Sign up to set email alerts
|

PERBEDAAN DAYA HAMBAT OBAT ANESTESI LOKAL LIDOCAINE 2% DAN ARTICAINE 4% TERHADAP PERTUMBUHAN BAKTERI Porphyromonas gingivalis SECARA IN VITRO

Abstract: Porphyromonas gingivalis is a  gram-negative anaerobic bacteria which is an oral normal microflora located in subgingival area.This bacteria can cause inflamation and delayed wound healing after dental invasive procedures. Lidocaine 2% and articaine 4% are the most used anaesthetic agents in dentistry. Both of these agents have been studied for having antibacterial effect in certain concentrations. This will open the possibility of using local anaesthetic agents as antibacterial agent in dental invasive proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…However, the closure of the diameter zone of the 20% w/v is relevanted with 15% w/v. According to Muharammy et al (2016) that the ability inhibitory zone of the compound as an antibacterial is shown that the 15-20 mm range is categorized in moderate hamps. While the inhibitory diameter zone more than 20 mm shows the power of stronger.…”
Section: Antibacterial Test Against S Epidermidismentioning
confidence: 99%
“…However, the closure of the diameter zone of the 20% w/v is relevanted with 15% w/v. According to Muharammy et al (2016) that the ability inhibitory zone of the compound as an antibacterial is shown that the 15-20 mm range is categorized in moderate hamps. While the inhibitory diameter zone more than 20 mm shows the power of stronger.…”
Section: Antibacterial Test Against S Epidermidismentioning
confidence: 99%
“…Bahan anestesi lokal terbagi atas dua golongan yaitu ester dan amida. (6,7,8,9) Anatesi lokal adalah cara yang paling aman dan paling efektif dalam manajemen nyeri bahan anestesi lokal dapat menghilangkan rasa sakit yang timbul akibat prosedur kedokteran gigi yang dilakukan. Anastesi lokal memblok saraf perifer yang kemudian mencegah rasa sakit, selama dan setelah prosedur bedah.…”
Section: Pendahuluanunclassified
“…Pada bidang kedokteran gigi lidokain sering ditambahkan adrenalin, adrenalin ini berfungsi sebagai vasokonstriktor yang dapat mempercepat mula kerja obat, meningkatkan lama kerja larutan anestesi lokal, menurunkan konsentrasi puncak larutan, anestesi di dalam darah sehingga toksisitas obat berkurang, memperkecil volume pemakaian larutan anestesi lokal, meningkatkan kedalaman efek anestesi lokal dan meningkatkan efektivitas larutan anestesi lokal. (10,12,9) Berdasarkan latar belakang di atas, peneliti tertarik untuk meneliti perbandingan efektivitas kerja anestetikum lidokain dan lidokain + epinefrin terhadap rasa nyeri pada pasien di RSIGM UMI sehingga dapat dijadikan pertimbangan dan dapat digunakan sebagai panduan penelitian selanjutnya.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation